A Practical Method of Second Order Analysis Part 2; Rigid Frames - LeMessurier, William J. (Engineering Journal, 1977)
In Part 1 of this series, a method was developed for performing second order analyses of pin jointed systems. A key concept of the method involved the lateral stiffness parameter lateral force which was defined as the force applied at the end of a member or subsystem that produces unit rotational displacement of the member or subsystem. This paper has developed a method for analyzing one-story rigid frames and multistory frames which are reasonably regular from floor to floor.